Cinnamic Acid in Frankincense Sap as a Criterion for Determining the Best Mother Plant for Vegetative Propagation of Styrax benzoin (Sumatra Benzoin) in Sumatra, Indonesia - Isnaini Nurwahyuni; Benardo Nababan; Svencer Pangoloi; Manihar Situmorang (International Journal of Forestry Research)
Cinnamic acid, contained in frankincense sap produced by Styrax benzoin (Sumatra benzoin tree), is an important compound that is used for various purposes, such as preservatives, fragrances, cosmetics, and pharmaceutical products. The production of frankincense sap as a forest product can be increased through the inclusion of S. benzoin seeds, which are propagated from the best mother plants. This study aims to use the content of cinnamic acid contained in the sap of S. benzoin as a criterion for determining the best mother plant for propagation of seeds. The research was conducted using healthy plants, taking sap samples, identifying and confirmation of cinnamic acid levels, and determining the best mother tree based on the content of cinnamic acid. The results of this study have identified six individual S. benzoin trees of very good quality based on their phenotypic advantages and the quantity of sap production. Isolation and identification of cinnamic acid from frankincense samples showed that the composition of cinnamic acid was high (12 to 21%). Three good quality S. benzoin trees, with high cinnamic acid composition, were SBN-7 (21%), SBN-3 (18%), and SBN-10 (17%). The SBN-7 tree was then chosen as the best S. benzoin, producing 2.70 kg year−1 sap, containing cc. 21% cinnamic acid. A selected mother plant will be used as a source of plant material for vegetative propagation to produce good quality seeds similar to the properties of the parent plant forforest conservation and to increase the production of nontimber forest raw materials for medicine and other purposes. The finding of this study is the first to use the composition of cinnamic acid as a criterion for determining the best mother plant. The composition of cinnamic acid in the sap is an important parameter in determining the superiority of S. benzoin plants.